2016
DOI: 10.1002/ccd.26801
|View full text |Cite
|
Sign up to set email alerts
|

A prospective evaluation of a standardized strategy for the use of a polymeric everolimus‐eluting bioresorbable scaffold in ST‐segment elevation myocardial infarction: Rationale and design of the BVS STEMI STRATEGY‐IT study

Abstract: This will be the first study investigating the feasibility and the early- and long-term clinical impact of a prespecified BVS implantation protocol in thrombotic lesions causing STEMI. Here, we describe the rationale and the design of the study. © 2016 Wiley Periodicals, Inc.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
5
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 30 publications
0
5
0
Order By: Relevance
“…However, bigger studies and registries enrolling patients receiving BRS with a standardized implantation technique are clearly on demand, especially in complex settings such as acute coronary syndrome or long lesions requiring overlap (30).…”
Section: Discussionmentioning
confidence: 99%
“…However, bigger studies and registries enrolling patients receiving BRS with a standardized implantation technique are clearly on demand, especially in complex settings such as acute coronary syndrome or long lesions requiring overlap (30).…”
Section: Discussionmentioning
confidence: 99%
“…As for the ideal patient for BVS, 31% considered patients younger than 75 years and admitted for ST-segment elevation myocardial infarction as good candidates for scaffold implantation, while 35% of them preferred patients with target vessel diameter between 3 and 3.6 mm, and 9% of them preferred patients in whom left anterior descending artery is involved (12). A minority of the operators (18%) did not consider scaffold implantation a possible choice in patients admitted to hospital for ST-segment elevation myocardial infarction (Figure 3).…”
Section: Future Perspectives On Bvsmentioning
confidence: 99%
“…In addition to the primary endpoint, the authors include sundry secondary endpoints: rates of procedural success; DOCE at extended follow‐up; definite or probable BVS thrombosis; bleeding; cardiac death; target vessel myocardial infarction; and ST‐segment resolution within 60 min of PPCI. The authors dictate specifics of patient care including antiplatelet regimen (dual antiplatelet therapy must be continued for 1 year and preferably with prasugrel or ticagrelor); use of thrombus aspiration (recommended if baseline TIMI flow is 0 or 1 or baseline TIMI flow of 2–3 with high thrombus burden on initial angiography); appropriate sizing of BVS (intracoronary imaging is not a requirement in this study); and how pre‐dilation and post‐dilation is to be performed . Notably these recommendations parallel Abbott's Instruction for Use (IFU).…”
mentioning
confidence: 99%
“…They quote a recent meta‐analysis which showed that following a BVS‐implantation protocol could significantly reduce the early and 12‐month incidence of device thrombosis . Ielasi et al are also strong believers in the theoretical advantages of BVS over traditional metallic stents. They point to the caging of the coronary wall at the site of drug‐eluting stent (DES) implantation and the loss of vasomotion associated with metallic stent implantation.…”
mentioning
confidence: 99%